Impact of Stress on Gamma Oscillations in the Rat Nucleus Accumbens During Spontaneous Social Interaction - Iturra-Mena, Ann Mary; Aguilar-Rivera, Marcelo; Arriagada-Solimano, Marcia; Pérez-Valenzuela, Catherine; Fuentealba, Pablo; Dagnino-Subiabre, Alexies (Frontiers in Behavioral Neuroscience, 2019)
Alteration in social behavior is one of the most debilitating symptoms of major depression, a stress related mental illness. Social behavior is modulated by the reward system, and gamma oscillations in the nucleus accumbens seem to be associated with reward processing. In this scenario, the role of gamma oscillations in depression remains unknown. We hypothesized that gamma oscillations in the rat nucleus accumbens are sensitive to the effects of social distress. One group of male Sprague-Dawley rats were exposed to chronic social defeat stress while the other group was left undisturbed (control group). Afterward, a microelectrode array was implanted in the nucleus accumbens of all animals. Local field potential activity was acquired using a wireless recording system. In an open field chamber, where implanted rats were placed by themselves for a non-social interaction condition, followed by introducing another unfamiliar rat, creating a social interaction condition, where the implanted rats interacted freely and continuously with the unfamiliar conspecific in a natural-like manner. We found that the high-gamma band power in the nucleus accumbens of non-stressed rats was higher during the social interaction compared to a non-social interaction condition. Conversely, we did not find significant differences at this level in the stressed rats when comparing the social interaction- and non-social interaction condition. These findings suggest that high-gamma oscillations in the nucleus accumbens are involved in social behavior. Furthermore, alterations at this level could be an electrophysiological signature of the effect of chronic social stress on reward processing.